Skimming and Scanning Techniques for Reading Comprehension - Ayu Wandira; Muhammad Candra; Dewi Murni (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
This study aimed to describe how the skimming and scanning techniques could improve the students’ reading comprehension at the IX-F grade students of SMP Negeri 16 Tanjungpinang in the academic year 2021/2022. The subject of this study consisted of 20 female students and 16 male students. This study employed Classroom Action Research (CAR). The kinds of data analyzed using qualitative and quantitative analysis. The quantitative data were from preliminary study, reading comprehension test I, and reading comprehension test II. Meanwhile, the qualitative data were obtained from the observation sheet. The quantitative data of the preliminary study showed that there were 6 of 36 students (17%) got score ?70. In test cycle I, the number of students who got score ?70 was 22 of 36 students (61%). In test cycle II, the students who got score ?70 were 28 of 36 students (77%). Based on the quantitative data, the improvement of students’ reading comprehension achieved the criteria success of this study. Furthermore, the qualitative data from the observation sheet showed that the skimming and scanning techniques improved the students’ participation and enthusiasm. So, it could be concluded that the skimming and scanning techniques improved students’ reading comprehension of Narrative text at the ninth grade students of SMP Negeri 16 Tanjungpinang